Small, big or medium sized organisations? The associations between span of control, leader identity and transformational leadership in Danish daycare - Bro, Louise Ladegaard (Politica, 2016)
Leaders of public organizations do not always have the same opportunities to lead. Depending on the size of the span of control, leaders might either find it difficult to effectively lead all individual employees (broad spans of control) or become so familiar with the employees and involved in the daily routines (narrow spans of control) that certain leadership strategies are hard to exert. Using quantitative data from the Danish daycare sector, this article finds that the levels of employee-perceived transformational leadership is greatest in medium-sized organizations (12-20 employees), and that the daycare leaders’ general leadership identity – as opposed to an identity as a pedagogue – explains the difference between organizations with narrow and medium-sized spans of control.